Effectiveness of cryptocurrency regulations on the security and financial well-being of investors in Tacloban City - Esmale, Nick Prince A.; Tarre, Krystel Erika M.; Teodoro, Pamela Kate M.; Ungab, Hannah Cassandra G.
This study assessed the effectiveness of cryptocurrency regulations, focusing on their impact on the security and financial well-being of investors in Tacloban City. With the rapid global adoption of cryptocurrencies, driven by technological advancements and market expansions, this research showed how cryptocurrency regulations align with investor protections against fraud and financial losses. Using a mixed-method design, this study began with qualitative insights from government agency interviews and document analysis, followed by a quantitative phase involving questionnaires distributed to local cryptocurrency investors. Findings revealed that a notable lack of detailed provisions for cryptocurrency transactions suggests the regulatory framework is insufficient for the evolving digital landscape. Differences between BSP, SEC, and the users' perspectives on investor awareness underscore potential regulatory misunderstandings. Quantitative results indicate increased investor awareness of regulations correlates with decreased perceived security, highlighting the need to address regulatory deficiencies to bolster confidence. Conversely, better regulatory knowledge enhances investors' financial well-being by giving them greater control over transactions. Moreover, as cryptocurrencies gain traction in the Philippines, the study underscores the urgency for a solid regulatory framework to protect the interests of its users and regulators, particularly in terms of inter-agency and international collaboration, cybersecurity, and investor education.